Isolation and characterization of bacteria isolates from soil feeding termites and soil from Juja and Kakamega forest in Kenya - Ntabo, R.; Boga, Hamadi I.; Muigai, A.; Mwirichia, R. (My University, 2010)
In the last several years information on the gut ecosystem of termites has continued to be gathered. Most studies have been focused on wood feeding termites but studies on soil feeders remain sparse owing to their difficulty of establishing permanent laboratory cultures. The aim of this study was to isolate, characterize and identify bacteria resident in the soil feeding termite gut, mound and parent soil of Cubitermes species with the potential to produce antibiotics and enzymes for industrialization. The samples were collected from kakamega forest from two sites Kalunya Glade and Lirhanda Hill. The study was also extended to the soils found in Juja. Hundred and thirty seven (137) isolates were cultivated and isolated using dilute nutrient agar media and screened for their antagonistic effects on various test organisms. Fifty one percent of the isolates were antagonist to Escherichia coli. Fifty seven percent of the isolates were antagonists to Bacillus subtilis while 55% of the isolates were antagonist to Candida albicans. Enzymatic activities of the isolates showed that 65% of the total isolates were starch degraders, 54% were casein degraders and 68% of the isolates were able to liquefy gelatin. Eleven percent of the isolates were cellulose degraders the majority of which were obtained from termite gut and mound. Isolates from Juja soil had the highest number of non degraders as compared to Kakamega Forest soils. The isolates were characterized using morphological, biochemical and molecular methods. Phylogenetic analysis of amplified 16S rRNA gene sequence revealed majority of the isolates were closely related to Bacillus and Brachybacterium species and had showed invitro antagonistic effects. Gram negative bacterial isolates obtained were closely related to Pseudomonas species. In conclusion, the isolates were potential antibiotic producers with varying ability to degrade gelatin, casein, and cellulose an indication of the role they play in their habitat
Keywords: DNBA; colony forming unit; mound; gut; surrounding soil; Kalunya; Lirhanda hill; Juja